The color of child survival in Colombia, 1955–2005. Issue 2 (17th February 2018) - Palacio Chaverra, Andrés
ABSTRACT: Objective(s): Colombia has the third largest black population in the Americas after Brazil and the USA. In 2005 mortality rate under 5 in Colombia was 21.5 per 1000, with a reduction of 82% between 2005 and 1955. That rate is not in line with rates for Cuba (6.8), Chile (9.1) or Costa Rica (10.4). Here we aim to provide evidence that a further reduction of child mortality relates to the unspoken racial gap in a pioneering country in family planning and praised in the 2000 WHO report as having the world's fairest health care reform in terms of coverage and financial access. Design: The lack of nationally representative data to estimate black/white differences in child mortality is overcome by using the ratio of children born and alive as the measure of mortality and the 2005 census data from IPUMS-I, which provides racial categories based on self-identification. The working sample contains 617, 985 mothers between 15 and 49 years of age, of whom 7.7% have experienced the death of at least one child. Using individual weights, a logistic regression is regressed on race, individual and community socio-economic status (SES), and demographic variables. Second, a model by cohort is regressed to capture the evolution of the racial gap over time. Third, interactions are run to examine the racial gap across SES groups. Results: The chances of losing a child are over 25% higher among black mothers relative to white mothers after controlling for individual and community SES characteristics. The racial gap remains stagnant and high for the period 1955–2005. The racial gap also is robust to changes in education and income levels. Conclusion: Failing to account for race slows down the improvement of child survival in Colombia relative to other countries of the region.